The army and their struggle with nature according to the chronicles of Anonym called Gall and Master Wincenty called Kadłubek - Ćwikła, Łukasz (Armia kontra natura, 2020)
The components of natural environment were suitable for defending the points of resistance or surprising the enemy. However, it is important to say that without a well prepared defense they were useless. For instance the role of forests wastwofold taking into account leading the great campaigns or even smaller skirmishes. The main issue of this article is to follow the army’s struggle with nature during marching and warfare (the aggression against Bohemia, Prussia and battles in the country) including its impact on both successes and defeats according to the chronicles of Anonym called Gall and Master Wincenty called Kadłubek.